Epidemiological Study of Tropical Diseases in Coastal Communities in the Context of Global Climate Change, in Kandai District, Kendari City - Hariati Lestari; Intan Tiara; Dhea Resky Apriana; Siti Sofia Hartin; Sarliani; Liberthy Mendila Tappo; Ririn Ali Rahmin; Sarnilawati; Safira (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Global climate change has emerged as a critical issue with far-reaching implications for human health, particularly in coastal regions. Coastal communities are especially vulnerable to the emergence and spread of tropical diseases due to environmental changes induced by climate variability and extremes. Objective: This study aims to analyze the factors influencing the incidence of tropical diseases in coastal communities within Kandai District, Kendari City, and to identify appropriate preventive strategies to mitigate associated health risks. Methods: A quantitative approach was employed using a cross-sectional study design. Data were collected from 200 respondents through the administration of structured questionnaires and direct interviews. The collected data were analyzed using univariate and bivariate statistical methods to examine relationships between variables. Results: The findings indicate that sanitation conditions, access to clean water, and community health behaviors are significantly associated with the incidence of tropical diseases. While the majority of respondents did not report malaria cases, instances of dengue fever were identified among the study population. Conclusion: The study demonstrates a strong correlation between environmental conditions and health-related behaviors with the prevalence of tropical diseases in coastal communities. Effective prevention requires integrated efforts focused on health promotion and the improvement of sanitation infrastructure to reduce the health burden posed by climate change. Keywords: Climate Change, Tropical Diseases, Coastal Communities, Sanitation, Public Health